1985
DOI: 10.1037/0021-843x.94.2.115
|View full text |Cite
|
Sign up to set email alerts
|

Cyclothymia in the adolescent offspring of parents with bipolar affective disorder.

Abstract: The present study explored the prevalence and types of psychopathology exhibited by the adolescent and young-adult offspring (ages 15-21) of patients with bipolar affective disorder. The major hypothesis of the study was that the offspring of bipolar patients would be characterized by an increased rate of cyclothymia. Subjects included 37 offspring of patients with bipolar affective disorder and 22 offspring of patients with nonaffective psychiatric disorders. Offspring received structured diagnostic interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
101
1
2

Year Published

1986
1986
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(106 citation statements)
references
References 65 publications
2
101
1
2
Order By: Relevance
“…Family studies of probands with ADHD and BD have supported this comorbidity as representing a familial type of early-onset BD. Klein et al [1985] 37 (24) Hammen [1990] 18 (14) 0 1 (6) 13 (72%) ***** All mothers with BD. 82% of unipolar comparison group with psychopathology Radke-Yarrow [1992] 44 (22) (56%) ****1/2 Results from subjects 8-11 years old reported here Carlson and Weintraub [1993] 128 6/125 (5%) 39 (30%) (at baseline) ?…”
Section: Phenomenological Studies Of Bipolar Offspringmentioning
confidence: 99%
See 1 more Smart Citation
“…Family studies of probands with ADHD and BD have supported this comorbidity as representing a familial type of early-onset BD. Klein et al [1985] 37 (24) Hammen [1990] 18 (14) 0 1 (6) 13 (72%) ***** All mothers with BD. 82% of unipolar comparison group with psychopathology Radke-Yarrow [1992] 44 (22) (56%) ****1/2 Results from subjects 8-11 years old reported here Carlson and Weintraub [1993] 128 6/125 (5%) 39 (30%) (at baseline) ?…”
Section: Phenomenological Studies Of Bipolar Offspringmentioning
confidence: 99%
“…Phenomenological bipolar offspring studies published between 1983 and 1993 [Kuyler et al, 1980;Waters and Marchenko-Bouer, 1980;LaRoche et al, 1981LaRoche et al, , 1985LaRoche et al, , 1987Decina et al, 1983;Gershon et al, 1985;Kashani et al, 1985;Klein et al, 1985;Hammen et al, 1987Hammen et al, , 1990Weintraub, 1987;Zahn-Waxler et al, 1988;Nurnberger et al, 1988b;Grigoroiu-Serbanescu et al, 1989;Radke-Yarrow et al, 1992;Carlson and Weintraub, 1993] were analyzed in a meta-analysis [Lapalme et al, 1997] (Table I). Of these 17 studies, 11 also included a comparison group of offspring of parents with no major mental disorder.…”
Section: Phenomenological Studies Of Bipolar Offspringmentioning
confidence: 99%
“…A number of studies have failed to find evidence of a link between parental depression and offspring suicidality (e.g., Grigoroiu-Serbanescu et al, 1989;Klein, Depue, & Slater, 1985;O'Connell, Mayo, O'Brien, & Misrsheidaie, 1979;Waters & Marchenko-Bouer, 1980;Weissman et al, 1984). Differences are noted for suicidal risk in children of depressed parents when (a) suicidal risk is assessed as a broader continuum of thoughts or actions, (b) assessed across cumulative time points, or (c) large samples are available for study (e.g., Lewinsohn, Olino, & Klein, 2005;Weissman, Fendrich, Warner, & Wickramaratne, 1992;Welner, Welner, McCrary, & Leonard, 1977).…”
mentioning
confidence: 97%
“…Two cross-sectional studies showed that adolescents with a depressed parent suffered from psychosocial maladjustment (38) and experienced a significantly higher rate of affective disorder than adolescents of nonaffective psychiatric control parents (39).…”
Section: Maternal Depression and Developmental Outcome Of Adolescentsmentioning
confidence: 99%